Culture's Consequences: Comparing Values, Behaviors, Institutions, and Organizations Across NationsCulture's Consequences: Comparing Values, Behaviors, Institutions, and Organizations Across Nations (Second Edition), by HofstedeGeert. Thousand Oaks, CA: Sage, 2001 - Bhagat, Rabi S. (Academy of Management Review, 2002)
The article reviews the book “Culture's Consequences: Comparing Values, Behaviors, Institutions, and Organizations Across Nations,” Second Edition, by Geert Hofstede.